2000
DOI: 10.1038/sj.onc.1203801
|View full text |Cite
|
Sign up to set email alerts
|

Expression of PTEN in PTEN-deficient multiple myeloma cells abolishes tumor growth in vivo

Abstract: Biochemical abnormalities associated with the development of multiple myeloma have been di cult to de®ne especially in terms of demonstrating an in vivo e ect of suspected lesions. Herein, we have identi®ed such a defect associated with lack of expression of PTEN, a cellular phosphatase involved in the regulation of phosphatidylinositol phosphates (PIP's). In myeloma cells, PIP's are required for phosphorylation of Akt, a key event leading to inhibition of apoptosis. Loss of PTEN results in a failure to de-pho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(20 citation statements)
references
References 22 publications
1
19
0
Order By: Relevance
“…Several elements of the PI-3K pathway, including the PTEN tumor suppressor gene, Akt kinase, and Bad, have been demonstrated to affect myeloma cell growth both in vitro and in vivo. 17 However, additional elements downstream in these cascades and their functions in either proliferation or apoptosis have yet to be defined. Here, we have described experiments in which a number of downstream targets have been identified and functional correlates established for both MAPK and PI-3K pathways.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several elements of the PI-3K pathway, including the PTEN tumor suppressor gene, Akt kinase, and Bad, have been demonstrated to affect myeloma cell growth both in vitro and in vivo. 17 However, additional elements downstream in these cascades and their functions in either proliferation or apoptosis have yet to be defined. Here, we have described experiments in which a number of downstream targets have been identified and functional correlates established for both MAPK and PI-3K pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Also, regulation of Akt phosphorylation by the PTEN tumor suppressor gene is critical in tumor cell proliferation, as in vivo growth of a myeloma line lacking PTEN can be prevented by expression of normal PTEN protein following gene transfection. 17 The second pathway associated with IGF-I stimulation signals through the Shc, Grb-2, Sos complex, resulting in activation of Ras and subsequently the mitogen-activated protein kinase (MAPK) signaling cascade. Whereas at least part of the effect of the PI-3K pathway has been demonstrated to be associated with apoptosis, the role of additional members of this cascade, as well as those in the MAPK pathway, has, in terms of proliferation or apoptosis, not been defined in myeloma cells.…”
Section: Introductionmentioning
confidence: 99%
“…PTEN is a lipid phosphatase that dephosphorylates PIP3, decreasing Akt activation. [28][29][30] PTEN is considered to be a tumor suppressor gene given that loss of PTEN activity, as a result of deletion or mutation of the gene, is commonly found in solid tumors. However, although PTEN mutations can be found in some cases of MM, 28 loss of PTEN function is an uncommon pathway of malignant transformation in lymphoproliferative disorders.…”
Section: Thalidomide Increases Integrin-induced Akt Phosphorylation Imentioning
confidence: 99%
“…[28][29][30] PTEN is considered to be a tumor suppressor gene given that loss of PTEN activity, as a result of deletion or mutation of the gene, is commonly found in solid tumors. However, although PTEN mutations can be found in some cases of MM, 28 loss of PTEN function is an uncommon pathway of malignant transformation in lymphoproliferative disorders. 6,31 We found that thalidomide reduced fibronectin-induced PTEN phosphorylation in IM9 cells PTEN activation, which may reduce even more downstream effects of PI3-kinase in IM9 and cells expressing functional PTEN.…”
Section: Thalidomide Increases Integrin-induced Akt Phosphorylation Imentioning
confidence: 99%
“…Inactivation of PTEN, which negatively regulates the phosphatidylinositol 3-kinase (PI3K)-mediated phosphorylation of AKT and BAD, inhibits apoptosis. Inactivating mutations of PTEN were identified in two of eight HMCLs, and transfection of normal PTEN into one of these HMCLs inhibited tumor formation in mice (159,160).…”
Section: Other Genetic Abnormalitiesmentioning
confidence: 99%